2019
DOI: 10.1002/smll.201904732
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Immunophenotyping of Cell Populations with an Electronic Antibody Microarray

Abstract: presents opportunities in global health and telemedicine applications for cell-based diagnostics and health monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…22−24 In addition, several hurdles limit the application of the highly experience dependent technique, such as inevitable measurements errors, requirement of an extremely expensive instrument, and high-content data analysis. 25 Comparably, we report a simple, economic, and efficient alternative approach, an electrochemical phenotyping method, in this paper, that facilitates reliable, rapid, and low-cost characterization of stemlike phenotypes in breast cancer. To present the expression signatures of the stemlike biomarkers, we incorporated a DNA assembly machinein situ programmable DNA circuit (PDC)to construct topologically defined nanostructures at the biomolecular recognition interface, and permits ultrasensitive phenotypic assay by translating the target binding events to the quantitative signals from well-organized strand crossover events.…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…22−24 In addition, several hurdles limit the application of the highly experience dependent technique, such as inevitable measurements errors, requirement of an extremely expensive instrument, and high-content data analysis. 25 Comparably, we report a simple, economic, and efficient alternative approach, an electrochemical phenotyping method, in this paper, that facilitates reliable, rapid, and low-cost characterization of stemlike phenotypes in breast cancer. To present the expression signatures of the stemlike biomarkers, we incorporated a DNA assembly machinein situ programmable DNA circuit (PDC)to construct topologically defined nanostructures at the biomolecular recognition interface, and permits ultrasensitive phenotypic assay by translating the target binding events to the quantitative signals from well-organized strand crossover events.…”
Section: ■ Introductionmentioning
confidence: 95%
“…As such, compensation at the detectors and “gating” are always necessary to correct the signal spillover and outline the distribution regions of cell subpopulations. However, incorrect compensation could adversely affect the sensitivity and lead to the generation of unexpected cell subpopulations; there is a “gating” effect wherein a lack of standardized instrument setup requires reliance exclusively on the people with experience. In addition, several hurdles limit the application of the highly experience dependent technique, such as inevitable measurements errors, requirement of an extremely expensive instrument, and high-content data analysis . Comparably, we report a simple, economic, and efficient alternative approach, an electrochemical phenotyping method, in this paper, that facilitates reliable, rapid, and low-cost characterization of stemlike phenotypes in breast cancer.…”
Section: Introductionmentioning
confidence: 96%
“…and other researchers developed microfluidic platforms for electrophoresis and sample separation purposes at the beginning of the 1990s (Manz et al., 1990 ; Harrison et al., 1992 ; Mathies & Huang, 1992 ; Woolley & Mathies, 1994 ). Microfluidics was then used as a multidisciplinary breakthrough technology that was quickly established with wide applications as in environmental sensing (Vasudev et al., 2013 ; Pol et al., 2017 ), combinatorial chemistry (synthesis and assays) (Li et al., 2018 ; Liu et al., 2019 ), energy applications (Chen et al., 2018 ; De et al., 2020 ), micro-propulsion (Feng et al., 2015 ; Serrano et al., 2018 ), organ-on-a-chip technology (Sittadjody et al., 2021 ; Zheng et al., 2021 ), clinical diagnostics (Luo et al., 2005 ; Chango et al., 2006 ), and drug delivery (Bains et al., 2017 ; Soheili et al., 2021 ). This review focuses on the application of microfluidics in drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, an antibody microarray was successfully applied for the quality control of mesenchymal stem cells . Other research groups also reported the potential use of similar antibody microarrays in immunophenotyping. …”
Section: Introductionmentioning
confidence: 99%